PENGARUH PEMUPUKAN ORGANIK TERHADAP PRODUKSI DAN MUTU TIGA NOMOR HARAPAN TEMULAWAK (Curcuma xanthorriza Roxb.) DI CIBINONG BOGOR - Mono Rahardjo; Nur Ajijah (Buletin Penelitian Tanaman Rempah dan Obat, 2007)
The Effect of Organic Fertilizer on Productivity and Quality of Three Promising Lines Java Turmeric (Curcuma Xanthorriza Roxb.) Promising Lines, in Cibinong BogorProductivity and quality of java tur-meric were influenced by many factors, i.e. nutrition availability from fertilizer appli-cation. The objective of the research was to examine the effect of organic fertilizer on rhizome productivity and quality of three java turmeric promising lines (Balittro 1, Balittro 2 and Balittro 3). The research was conducted in Cibinong Experimental Garden, from No-vember 2005 until October 2006. The organic fertilizer application were 10 t/ha bookashi + 90 kg/ha bio fertilizer + 300 kg/ha zeolit + 300 kg/ha rock-phosphate/ha. Experiment was arranged in Randomized Block Design with 9 replications. Plot size of experiment is 30 cm2, with plant distance are 75 cm x 50 cm. Each plot contain 80 plants. The result showed that the rhizomes yield of three genotypes of java turmeric Balittro 1, Balittro 2 and Balittro 3 (ranged for 14.21 - 16.59 ton/ha) was higher than the rate of national production (10.7 ton/ha). The production of rhizomes, xanthor-rizol and curcuminoid of Balittro 1 were higher than  Balittro 2 and Balittro 3. The Balittro 1 promising line was superior java turmeric due to its higher response to organic fertilizers.